Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.4049/jimmunol.1103253
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: LPS-Induced Emergency Myelopoiesis Depends on TLR4-Expressing Nonhematopoietic Cells

Abstract: Systemic bacterial infection is rapidly recognized as an emergency state leading to neutrophil release into the circulation and increased myeloid cell production within the bone marrow. However, the mechanisms of sensing infection and subsequent translation into emergency myelopoiesis have not been defined. In this study, we demonstrate in vivo in mice that, surprisingly, selective TLR4 expression within the hematopoietic compartment fails to induce LPS-driven emergency myelopoiesis. In contrast, TLR4-expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
136
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(149 citation statements)
references
References 32 publications
(22 reference statements)
10
136
0
3
Order By: Relevance
“…The enhanced engraftment potential of hematopoietic progenitors from Edil3 -/-mice was linked to a diminished potenneally injected with ultra-pure LPS twice, with an interval of 48 hours, and hematopoietic progenitors and myeloid lineage cells were analyzed at 24 hours and at 72 hours following the second injection (52,53). In this model, the initial increase in peripheral blood myeloid cells (52,53), associated with a decrease in the numbers of mature myeloid cells and CMPs in the BM, is followed by a prominent expansion of the myeloid cell compartment, as observed in Edil3 +/+ mice at 72 hours after LPS administration (Figure 8, A and B). However, the restoration of myelopoiesis in the BM was significantly attenuated in Del-1 deficiency, as shown by the decreased numbers of Gr1 hi…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced engraftment potential of hematopoietic progenitors from Edil3 -/-mice was linked to a diminished potenneally injected with ultra-pure LPS twice, with an interval of 48 hours, and hematopoietic progenitors and myeloid lineage cells were analyzed at 24 hours and at 72 hours following the second injection (52,53). In this model, the initial increase in peripheral blood myeloid cells (52,53), associated with a decrease in the numbers of mature myeloid cells and CMPs in the BM, is followed by a prominent expansion of the myeloid cell compartment, as observed in Edil3 +/+ mice at 72 hours after LPS administration (Figure 8, A and B). However, the restoration of myelopoiesis in the BM was significantly attenuated in Del-1 deficiency, as shown by the decreased numbers of Gr1 hi…”
Section: Discussionmentioning
confidence: 99%
“…LPS is an inflammation-inducing compound that activates stromal cells in the BM and spleen via TLR4. 18,19) Thus, LPS-treated mice are an appropriate experimental model to study how the bal- ance of positive and negative factors between B lymphopoiesis and myelopoiesis induced by stromal cells is altered during inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased LPS caused by Gram-negative infection initiates emergent granulopoiesis by activating stromal cells to release cytokines such as G-CSF. 18,19) Several in vitro studies showed that positive-and negative-regulator of B lymphopoiesis interact with each other. TNF-α down-regulated the expression of SDF-1 by stromal cell, 20) TGF-β also down-regulated the expressions of SDF-1, SCF and IL-7.…”
mentioning
confidence: 99%
“…3,4) This reciprocal regulation of myelopoiesis and B lymphopoiesis after LPS treatment is likely an indirect effect via stromal cells rather than a direct effect of LPS on hematopoietic cells. 5,6) Several groups recently used the mouse model of repeated low-dose LPS exposure and reported that chronic TLR signaling alters hematopoietic components. [7][8][9] Chronic (repeated) exposure of mice to LPS reduces lymphoid cells and skews the hematopoietic cell compartment toward myeloid cells, circumstances that resemble the phenotype of aged mice.…”
mentioning
confidence: 99%